AN ASSESSMENT OF THE IMPACT OF RURAL DEVELOPMENT POLICIES IN NIGERIA - LERE, ISHAKU BITRUS; TAYEB, AZMIL (International Journal of Psychosocial Rehabilitation, 2020)
The bulk of the population of most countries of the world is residing in rural areas, hence the advancement of the local regions remains the prerogative of every administration. Thus, the advancement of the local areas of Nigeria pursed a severe predicament to development experts, policymakers, which continued unresolved. The methodology that was used in this research work was the trend and the content analysis approach. The data were derived from secondary sources. It revealed that the Nigerian government, since independence in 1960, has initiated and embarked on the plethora of rural development programs that have been overwhelmingly mired by some success and challenges. It further revealed that the policies have high aims and objectives, but the major problem has been the implementation. The condition was made difficult by the ruling class who hijacked the monies meant for these programs for their pockets. The paper recommends that; the existing political system should be checked by strengthening anti-craft institutions. The anti-craft institutions will checkmate the activities of the ruling class in Nigeria, the adoption of a decentralized model and people-driven rural advancement program, a panacea to the rural growth program within the country.